دراسة تحليلية لضريبة الرواتب والأجور في سوريا - الصطوف محمد الحسين; الـخلـف محمــد; ركاج يحـيـى محمـد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تحظى الضرائب باهتمام كبير في دول العالم بشكل عام، وفي سوريا بشكل خاص في ظل مسيرة التطوير والتحديث التي يشهدها القطر، وتتركز أهمية هذا الاهتمام في تنمية الوعي لدى المواطنين والعمل على تغيير المقولة القديمة التي شبهت واضع ومنفذ السياسة الضريبية بالذي يستطيع أن ينتف ريش الإوزة بدون أن يجعلها تصرخ، لذلك حاولنا في هذا البحث الوقوف على ملامح النظام الضريبي ودراسة ضريبة الرواتب والأجور المطبقة في سوريا من حيث الإيرادات والعدالة لما تتمتع به من أهمية خاصة كونها تصيب شريحة كبيرة في المجتمع -حيث أن 49.23% من العاملين في سوريا هم من العاملين بأجر في عام 2001 - ولصعوبة التهرب منها، ولما تمثله من وسيلة مباشرة وفعالة في الحد من الاستهلاك وتقليل التفاوت بين الطبقات وتشجيع الادخار والاستثمار، وقد تضمن البحث نقاطا عدة وهي: ملامح النظام الضريبي السوري. ماهية ضريبة الرواتب والأجور في سوريا. تطور إيرادات ضريبة الرواتب والأجور في سوريا. العدالة الضريبية في مجال ضريبة الرواتب والأجور في سوريا. Taxes are generally given high priority by all governments, but in Syria, in particular, concern with taxes is part of the process of development and modernization the country is currently witnessing. The Syrian government’s policy is to raise people’s consciousness and change their preconceptions about the country’s taxation system. Thus, the paper tries to explain the characteristics of the tax system, with particular emphasis on taxes on salaries and wages in terms of revenues and fairness. This is because a great number of people is affected: 49.23% of workers in 2001 in Syria were wage earners. Moreover, taxes on wages are unavoidable and represent a direct and effective means of limiting consumption, narrowing the gap between classes, and encouraging savings and investment. The study includes the following points: Features of the Syrian tax system. The essence of taxes on salaries and wages in Syria. Increase of revenues from taxes and wages in Syria. Fairness of taxes on wages and salaries in Syria.